Assessment of combined nutrients and pesticides grey water footprint in a Sub-Saharan African lake catchment - Onyango, J.; Simaika, John; Kitaka, N.; Irvine, K. (Elsevier, 2025)
Water scarcity and pollution are pressing challenges in agricultural catchments. This study quantified the Grey Water Footprint (GWF) of nutrients and pesticide residues in the Lake Naivasha catchment, Kenya, and assessed spatial patterns of pollution stress. Mean daily discharge ranged from 0.03 ± 0.01 m3 s−1 at Little Gilgil (G2) to 2.95 ± 1.78 m3 s−1 at Malewa Highway Bridge (M5). The highest nutrient-related GWF was recorded for total phosphorus at Karati (K1), 5.3 × 106 ± 1.6 × 106 mm3 year−1, while the lowest values were observed at the downstream Malewa sites (M4 and M5). For pesticides, cyclodienes peaked at K1 with values ranging from 1.59 × 105 ± 3.52 × 104 mm3 year−1 for dieldrin to 81.9 ± 32.7 mm3 year−1 for methoxychlor, while DDT and HCH groups ranged from 0.34 ± 0.08 mm3 year−1 for γ-HCH at Malewa to 3.80 × 106 ± 1.67 × 106 mm3 year−1 for pp-DDT at Karati. The Integrated Grey Water Footprint (IGWF) showed that pesticides dominated pollution stress at most sites, except Karati where phosphorus loads were highest. Grey Water Stress (GWS) exceeded unity (>1) at Karati, indicating that pollutant loads surpassed the river's assimilative capacity, while other sites remained below capacity, ranging from 2 to 4 % at Malewa (M1) to 10–20 % at Little Gilgil (G2). These findings highlight pollution hotspots in low-flow sub-catchments, driven by intensive farming and settlements, and underscore the urgent need for integrated water quality standards and advanced monitoring strategies to safeguard aquatic ecosystems and promote sustainable water management in sub-Saharan Africa.